Hubungan Motivasi Perawat Dengan Penerapan Post Conference Di RSUD Undata Provinsi Sulawesi Tengah - Hotnida Hotnida; Masri DG Taha; Viere Allanled (Universitas Widya Nusantara, 2024)
Motivation is a support, desire or interest that is so great within, to achieve a desire, ideals and certain goals. Conference is a small group discussion conducted by nursing staff at every shift change. Conferences are conducted before (pre-conference) or after handover (post-conference). The implementation of conference has an impact on nurses' skills in reporting nursing care plans and outcomes during shift changes. Data on the implementation of conferences based on a study conducted on nursing in Singapore in 2015 showed a rate about 75.1%, while a study conducted in Iran in 2017, the implementation of clinical conferences was 45.5%. The purpose of both pre and post conferences are to share information, help nurses develop problem-solving and critical thinking skills, provide opportunities for nurses to develop collegial relationships, exchange ideas for specific purposes, share successes and failures in clinical practice. The purpose of this study was to determine the correlation between nurses motivation and the implementation of post conference in Seroja Ward at Undata Hospital, Central Sulawesi Province, the results found that there was a correlation between nurses motivation and the implementation of post conference at Undata Hospital, Central Sulawesi Province with a squere value of p=0.012 (p-value <0.05), then Ho was rejected and H1 was accepted.